Youth and Health as an issue of Research in Social Work - Two examples of current Research - Gabriele Stumpp (Social Work and Society)
Health issues under aspects pertaining to social work are currently being investigated in our department under two main perspectives. The study of Youth, Health, and Internet is based on experiences with a project of e-mail counseling for youths we have been running in our department for one year so far. Our thesis is that the internet has become an important platform for youngsters in general as well as concerning health issues specifically. So far, however, little is known about the ways youths address their health related problems in the net. We believe that research in this area is badly needed since future concepts of effective health improvement and prevention for youths cannot ignore this medium. Biography and Health is our second focus of investigation, addressing deficiencies in the empirical research of Aaron AntonovskyÂ´s salutogenetic concept that has lately become quite popular in many health discussions. Drawing from biographical methods we are currently investigating the development of the so called "sense of coherence" - the center piece of salutogenesis.